Effects of prenatal exposure to synthetic sex hormones on neurodevelopment: a biological mechanism. - Soyer-Gobillard, Marie-Odile; Gaspari, Laura; Paris, Françoise; Courtet, Philippe; Sultan, Charles (Frontiers in Molecular Neuroscience, 2023)
Since the middle of the 20th century, synthetic sex hormones (estrogens and progestins) have been administered to millions of women worldwide, mainly to avoid miscarriage or for comfort, although their mode of action and their effects on the mother and fetus were ignored. Despite the alerts and the description of somatic and psychiatric disorders in children exposed in utero, synthetic estrogens were prohibited for pregnant women only in the 1970s and 1980s, but some progestins are still authorized.In this review, we summarize the psychiatric disorders described in children exposed in utero to such hormones, focusing particularly on schizophrenia, bipolar disorders, severe depression, eating disorders, suicide and suicide attempts. Moreover, only in 2017 the mechanism of action of these xenohormones has started to be deciphered. Some studies showed that in the fetus exposed in utero, they alter the DNA methylation profile (mainly hypermethylation), and consequently the expression of genes implicated in neurodevelopment and in regulating the sexual organ morphogenesis and also of the promoter of estrogen receptors, located in the amygdala. These deleterious effects may be transmitted also to the next generations, thus affecting the children directly exposed in utero and also the following generations. As prenatal exposure to synthetic estrogens or/and progestins may trigger